Is increased screening and early antiretroviral treatment for HIV‐1 worth the investment? An analysis of the public health and economic impact of improvement in the UK. Issue 10 (8th August 2019) - Brogan, AJ; Talbird, SE; Davis, AE; Wild, L; Flanagan, D
Abstract : Objectives: Early treatment of HIV‐1 infection at all CD4 levels has demonstrated clinical and public health benefits. This analysis examined the costs, health outcomes, and cost‐effectiveness of increased HIV‐1 screening and early treatment initiation in the UK. Methods: A Markov model followed theoretical cohorts of men who have sex with men (MSM), heterosexuals, and people who inject drugs (PWID) with initially undiagnosed HIV‐1 infection over their remaining lifetimes. The analysis examined increased HIV‐1 screening (resulting in 10–50% improvements in diagnosis rates) versus current screening in sexual health services (SHS) and other settings, with all individuals initiating treatment within 3 months of diagnosis. Health status was modelled by viral load and CD4 cell count as individuals progressed to diagnosis and treatment. Individuals accrued quality‐adjusted life‐years (QALYs), incurred costs for screening and HIV‐related clinical management, and were at risk of transmitting HIV‐1 infection to their partners. Input parameter data were taken primarily from UK‐specific published sources. All outcomes were discounted at 3.5% annually. Results: The model estimated that increased screening and early treatment resulted in fewer onward HIV transmissions, more QALYs, and higher total costs. For SHS, incremental cost‐effectiveness ratios (ICERs) for heterosexuals (~£22 000/QALY gained) were within typical UK willingness‐to‐pay thresholds and were well below these thresholds for MSM (~£9500/QALY gained) and PWID (~£6500/QALY gained). Sensitivity analysis showed that model results were robust. Conclusions: Increased HIV‐1 screening and early treatment initiation may be a cost‐effective strategy to reduce HIV transmission and improve health for MSM, heterosexuals, and PWID in the UK.